High-temperature cooking resistant PE film and preparation method thereof

The high-temperature resistant retortable PE film prepared by composite materials and processes solves the problems of oxidation, yellowing, brittleness and microbial growth of traditional PE films during high-temperature cooking and long-term storage. It achieves high strength, barrier properties and antioxidant properties, and is suitable for the food packaging field.

CN121449989APending Publication Date: 2026-02-03JINZHIYANG (GUANGZHOU) NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510993717.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-18
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Traditional PE film is prone to oxidation during high-temperature cooking and long-term storage, causing the film to turn yellow and become brittle. At the same time, it cannot inhibit the growth of microorganisms, affecting the hygiene and safety of packaged goods.

Method used

A high-temperature resistant PE film is prepared by using a composite material composed of metallocene polyethylene, bio-based polyethylene, dicumyl peroxide, nano-silica, graphene nanosheets, and layered double hydroxides through blending, crosslinking, and film-forming processes. This results in a dynamic crosslinking network and a fluorine-containing protective layer, combined with the antioxidant and antibacterial properties of tea polyphenol-zinc complex.

Benefits of technology

It improves the tensile strength, tear strength, puncture resistance, barrier properties and antioxidant properties of the film, ensuring the hygiene and safety of packaged goods and their shelf life, while reducing dependence on traditional petroleum-based raw materials and meeting environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121449989A_ABST
    Figure CN121449989A_ABST
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials, and discloses a high-temperature-steaming-resistant PE (polyethylene) film and a preparation method of the high-temperature-steaming-resistant PE film. Comprising the following raw materials in parts by weight: 50-60 parts of metallocene polyethylene, 15-20 parts of bio-based polyethylene, 0.8-1.2 parts of dicumyl peroxide, 0.3-0.5 part of a cross-linking agent, 3-4 parts of nano silicon dioxide, 2-3 parts of layered double hydroxides, 0.5-1 part of graphene nanosheets, 8-12 parts of fluorine-containing polymer modified PE resin and 0.8-1 part of an organic tin-rare earth composite heat stabilizer. The shape and strength at high temperature are guaranteed through metallocene polyethylene and bio-based polyethylene, dicumyl peroxide is combined with a cross-linking agent to reinforce heat resistance and size stability, fluorine-containing polymer modified PE resin forms a fluorine-containing protective layer, an organic tin-rare earth composite heat stabilizer inhibits thermal degradation, a composite antioxidant captures free radicals, and the film is prevented from yellowing and embrittling.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high polymer materials, in particular to a high-temperature-resistant retort PE film and a preparation method thereof. BACKGROUND

[0002] In the modern packaging industry, with the increasing requirements of food, medicine and other fields for product preservation, quality preservation and convenience, the performance of packaging materials is crucial. Among them, high-temperature retort packaging can sterilize the product in a high-temperature and high-pressure environment, prolong the shelf life of the product, and maintain the flavor and quality of the product, and is widely used in the field of food packaging.

[0003] The traditional PE film is mainly based on ordinary polyethylene (PE) film, which is usually made of a single polyethylene resin through simple blowing or casting process. In the production process, only a small amount of conventional additives, such as general antioxidants, are added to prevent oxidative degradation during processing. Although it has certain flexibility and basic packaging function, it is prone to oxidative reaction during high-temperature retort and long-term storage, which causes the film to turn yellow and brittle, and cannot inhibit the growth of microorganisms, affecting the health and safety of packaged goods. SUMMARY

[0004] In view of the deficiencies of the prior art, the present application provides a high-temperature-resistant retort PE film and a preparation method thereof, which solves the problem that the traditional PE film is prone to oxidative reaction during high-temperature retort and long-term storage, which causes the film to turn yellow and brittle, and cannot inhibit the growth of microorganisms, affecting the health and safety of packaged goods.

[0005] To achieve the above purpose, the present application realizes the following technical scheme: a high-temperature-resistant retort PE film, comprising the following raw materials by weight: metallocene polyethylene 50-60 parts, bio-based polyethylene 15-20 parts, dicumyl peroxide 0.8-1.2 parts, crosslinking agent 0.3-0.5 parts, nano-silicon dioxide 3-4 parts, layered double hydroxide 2-3 parts, graphene nanosheet 0.5-1 part, fluorine-containing polymer modified PE resin 8-12 parts, organic tin-rare earth composite heat stabilizer 0.8-1 part, tea polyphenol-zinc complex 0.2-0.4 part, composite antioxidant 0.3-0.6 part, compatibilizer 4-6 parts, bio-based erucic acid amide slip agent 0.5-0.8 part, calcium stearate 0.8-1 part, nucleating agent 0.2-0.4 part, and nano-boehmite 1-2 parts.

[0006] Preferably, the compatibilizer includes maleic anhydride grafted SEBS, the nucleating agent is 1,3:2,4-bis(3,4-dimethylbenzylidene)sorbitol, the graphene nanosheet is surface modified by hydroxylation or carboxylation, the fluorine-containing polymer modified PE resin is ethylene-tetrafluoroethylene copolymer or polyvinylidene fluoride grafted modified polyethylene, and the mass fraction of fluorine element is 5-8%.

[0007] Preferably, the crosslinking agent includes simultaneously adding furan functionalized polymer and maleimide functionalized polymer in the polymer matrix, and the crosslinking agent triggers a diene addition reaction to form a dynamic crosslinking network during processing, the furan functionalized polymer is furan methylamine grafted polyethylene, the maleimide functionalized polymer is N-phenyl maleimide terminated polyethylene, the composite antioxidant is composed of a mass ratio of 1:1 of a hindered phenolic antioxidant and a phosphite antioxidant, and the bio-based polyethylene is bio-based HDPE prepared by fermentation of sugarcane ethanol or corn starch, and the melt index is 2-5 g / 10 min.

[0008] Preferably, the tea polyphenol-zinc complex is prepared by reacting tea polyphenol with zinc acetate at a molar ratio of 1:1-1:2, the nano-silicon dioxide has a particle size of 20-50 nm and is surface modified by silane coupling agent KH-550 or KH-570, the nano-boehmite has a particle size of 50-100 nm and a mass ratio of 1:1.5-1:2 with LDH, and the organotin-rare earth composite heat stabilizer is dibutyltin dilaurate compounded with cerium oxide at a mass ratio of 2:1-3:1.

[0009] A method for preparing a high-temperature resistant cooking PE film, comprising the following steps: S1, processing: the metallocene polyethylene and bio-based polyethylene are placed in an oven for drying to remove water, obtaining a dry body, the nano-silicon dioxide, graphene nanosheet, nano-boehmite, and layered double hydroxide are added to a proper amount of anhydrous ethanol for ultrasonic dispersion treatment to make them uniformly dispersed, obtaining a dispersion, and the fluorine-containing polymer modified PE resin, organotin-rare earth composite heat stabilizer, tea polyphenol-zinc complex, composite antioxidant, bio-based erucamide slip agent, calcium stearate, and nucleating agent are mixed uniformly by a high-speed mixer to obtain a mixture; S2, blending: the dry body is put into the main feeding port of the twin-screw extruder, the dispersion and the mixture as well as the compatibilizer are added to the twin-screw extruder through the side feeding device for sufficient melt blending; S3, crosslinking: the dicumyl peroxide is dissolved in toluene to prepare a solution, the solution is injected into the twin-screw extruder through a metering pump for preliminary crosslinking, and the crosslinking agent is injected for crosslinking reaction through another metering pump, and the screw rotation speed and the injection amount of the crosslinking agent are adjusted to control the crosslinking reaction time, obtaining a material; S4. Granulation: Control the twin-screw extruder to extrude the material, and granulate it by water-cooled stringing or underwater pelletizing. Control the pelletizer speed according to the particle size requirements to obtain granules. S5. Film Formation: The granular material is fed into a casting machine, and a flat film is prepared through the casting process. The film is then heat-treated in an oven to eliminate its internal stress, stabilize the dynamic cross-linking network, and complete the preparation.

[0010] Preferably, the temperature of the oven in S1 is 80-100℃, the drying time is 2-4 hours, the ultrasonic dispersion treatment is set to an acoustic frequency of 40-60kHz and an ultrasonic time of 30-60 minutes, and the high-speed mixer has a stirring speed of 800-1200r / min and a stirring time of 15-30 minutes.

[0011] Preferably, the screw temperature of the twin-screw extruder in S2 is 180-220℃, the screw speed is 200-300 r / min, the length-to-diameter ratio is 30-40, and the melt pressure is 8-12 MPa.

[0012] Preferably, the concentration of the solution in S3 is 10-15 wt%, the initial cross-linking region is in the region with a temperature of 150-170°C, and the cross-linking reaction time is 3-5 minutes.

[0013] Preferably, the extrusion rate in S4 is 10-40 kg / h, and the pelletizer speed is 100-200 r / min.

[0014] Preferably, in S5, the temperature of the casting machine is 180-210℃, the casting speed is 3-6m / min, the temperature of the cooling roller is 15-25℃, the temperature of the oven is 100-120℃, and the heat treatment time is 1-2 hours.

[0015] This invention provides a high-temperature resistant retortable PE film and its preparation method. It has the following beneficial effects: 1. This invention ensures the shape and strength of PE films at high temperatures through metallocene polyethylene and bio-based polyethylene, enhances heat resistance and dimensional stability through dicumyl peroxide and crosslinking agents, forms a fluorinated protective layer through fluoropolymer-modified PE resin, inhibits thermal degradation through organotin-rare earth composite heat stabilizers, captures free radicals through composite antioxidants to prevent the film from yellowing and becoming brittle, imparts antibacterial properties through tea polyphenol-zinc complex to ensure hygiene and safety, and refines grains through nucleating agents to improve transparency and rigidity. This solves the problems of traditional PE films during high-temperature cooking and long-term storage.

[0016] 2. This invention uses nano-silica to fill the spaces between molecular chains, enhancing the interaction between the molecular chains. Graphene nanosheets construct a highly efficient mechanical reinforcement network, which improves the tensile strength, tear strength, and puncture resistance of the film. During packaging and transportation, it can effectively resist external damage and provide reliable protection for packaged items.

[0017] 3. This invention forms a fluorinated protective layer on the film surface by modifying PE resin with fluoropolymer. With its low surface energy and chemical inertness, it improves the film's ability to block small molecules such as oxygen and water vapor, reduces gas and moisture permeability, and enhances chemical corrosion resistance, allowing the film to effectively resist the erosion of various chemical substances and extend the shelf life of packaged goods.

[0018] 4. By introducing bio-based polyethylene, this invention reduces reliance on traditional petroleum-based raw materials, practices the concept of sustainable resource utilization, and reduces the carbon footprint of the product. In addition, tea polyphenol-zinc complex, as a bio-based antioxidant, partially replaces traditional chemical antioxidants, ensuring antioxidant performance while being more green and environmentally friendly, which is in line with the current trend of green development.

[0019] 5. This invention improves production efficiency and ensures product quality stability and consistency by proceeding from the drying, dispersion and mixing of raw material pretreatment to melt blending, crosslinking, granulation and finally casting and heat treatment, which is conducive to large-scale industrial production. Attached Figure Description

[0020] Figure 1 This is a flowchart of a method for preparing a high-temperature resistant PE film proposed in this invention. Detailed Implementation

[0021] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] This invention provides a high-temperature resistant retortable PE film, comprising the following raw materials in parts by weight: 50-60 parts of metallocene polyethylene, 15-20 parts of bio-based polyethylene, 0.8-1.2 parts of dicumyl peroxide, 0.3-0.5 parts of crosslinking agent, 3-4 parts of nano-silica, 2-3 parts of layered double hydroxide, 0.5-1 parts of graphene nanosheets, 8-12 parts of fluoropolymer-modified PE resin, 0.8-1 parts of organotin-rare earth composite heat stabilizer, 0.2-0.4 parts of tea polyphenol-zinc complex, 0.3-0.6 parts of composite antioxidant, 4-6 parts of compatibilizer, 0.5-0.8 parts of bio-based erucic acid amide slip agent, 0.8-1 parts of calcium stearate, 0.2-0.4 parts of nucleating agent, and 1-2 parts of nano-boehmite.

[0023] Specifically, the addition of metallocene polyethylene improves the crystallinity and molecular chain regularity of the PE film, thereby enhancing the tensile strength, tear strength, and heat resistance of the film. This allows the film to maintain its good physical shape during high-temperature cooking and prevents it from cracking or deforming.

[0024] The addition of bio-based polyethylene reduces reliance on traditional petroleum-based polyethylene, achieving environmental protection and sustainable development. At the same time, the molecular structure of bio-based polyethylene endows the film with a certain degree of flexibility and good processing performance, making the film easier to handle during the molding process.

[0025] The addition of dicumyl peroxide decomposes at high temperatures to generate free radicals, which trigger cross-linking reactions between polymer molecular chains, thereby increasing the cross-linking density and network structure of the film. This helps to improve the thermal stability and mechanical properties of the film, making it more stable under high-temperature cooking conditions.

[0026] By adding a crosslinking agent, a dynamic crosslinking network is formed in the polymer matrix, which improves the elasticity, creep resistance and dimensional stability of the film, and prevents the film from shrinking or deforming during cooking.

[0027] The addition of nano-silica fills the spaces between polymer molecular chains, increasing the friction and interaction forces between the chains and improving the mechanical strength, barrier properties, and wear resistance of the film. At the same time, nano-silica can also improve the surface smoothness and gloss of the film.

[0028] By adding layered double hydroxides, the film decomposes and absorbs heat during combustion, releasing carbon dioxide and water vapor to achieve flame retardancy and smoke suppression. Furthermore, LDH can work synergistically with other flame retardants to improve the overall flame retardant performance of the film, making it safer in high-temperature cooking environments.

[0029] By adding graphene nanosheets, a highly efficient thermally conductive network is formed in the film, improving the film's thermal conductivity. This allows the film to quickly and evenly transfer heat during cooking, reducing localized overheating and improving cooking efficiency and product quality.

[0030] By adding fluoropolymer-modified PE resin, a fluorine-containing protective layer is formed on the film surface, which improves the film's chemical corrosion resistance, barrier properties, and surface hydrophobicity. This enables the film to resist the erosion of various chemicals, extend its service life, and facilitate cleaning and maintenance.

[0031] By adding organotin-rare earth composite heat stabilizers, the thermal degradation reaction of polymers during high-temperature processing and use is inhibited, thereby improving the thermal stability and aging resistance of the film. It can play a role in different temperature ranges and effectively prevent the film from turning yellow and brittle during cooking.

[0032] By adding tea polyphenol-zinc complex, the antioxidant and antibacterial properties of tea polyphenols are utilized to delay the oxidative degradation of the film and inhibit the growth of microorganisms, which helps to maintain the freshness and hygiene of the film and extend the shelf life of the product.

[0033] By adding composite antioxidants, free radicals are captured at different stages, the oxidation reaction is inhibited, and the antioxidant performance and service life of the film are improved. The hindered phenolic and phosphite antioxidants in the composite antioxidants work synergistically to more effectively protect the film from oxidative damage.

[0034] By adding compatibilizers, the compatibility between different polymers is improved, the interfacial tension is reduced, and the dispersion uniformity and binding force between the components are enhanced, resulting in more stable and uniform film performance and avoiding performance degradation caused by phase separation.

[0035] By adding bio-based erucamide slip agent, a lubricating film is formed on the film surface, which reduces the friction between films, improves the slip and opening properties of the film, and makes the film smoother and less prone to sticking during production, packaging and use.

[0036] The addition of calcium stearate acts as a lubricant and release agent, improving the processing performance and release effect of the film. Calcium stearate can reduce the friction between the polymer and the processing equipment, making it easier for the film to be released from the mold, thereby improving production efficiency and product quality.

[0037] The addition of nucleating agents provides more crystal nuclei during polymer crystallization, promoting crystal formation and growth, increasing the crystallinity and crystallization rate of the film, and helping to improve the film's transparency, rigidity, and heat distortion temperature.

[0038] By adding nano-boehmite, it decomposes and absorbs heat during combustion, releasing moisture to achieve flame retardancy and reduce smoke density. The synergistic effect of nano-boehmite and LDH further improves the flame retardant performance of the film, making it safer and more reliable in high-temperature cooking environments.

[0039] By combining various raw materials, the components work synergistically and complement each other, resulting in a high-temperature resistant retortable PE film with high heat resistance, good mechanical properties, excellent barrier properties, flame retardant properties, and antioxidant properties. This solves the problem that traditional PE films are prone to oxidation during high-temperature cooking and long-term storage, causing the film to turn yellow and brittle, and at the same time, they cannot inhibit the growth of microorganisms, affecting the hygiene and safety of packaged goods.

[0040] The compatibilizer includes maleic anhydride-grafted SEBS, the nucleating agent is 1,3:2,4-di(3,4-dimethylbenzylmethyl)sorbitol, the graphene nanosheets are surface-modified by hydroxylation or carboxylation, and the fluoropolymer-modified PE resin is ethylene-tetrafluoroethylene copolymer or polyvinylidene fluoride-grafted modified polyethylene, with a fluorine content of 5-8% by mass.

[0041] Specifically, by using a compatibilizer including maleic anhydride-grafted SEBS, the maleic anhydride groups in its molecular structure can chemically react with polar polymers, while the SEBS portion exhibits good compatibility with the non-polar PE matrix, enhancing the interfacial bonding between polar and non-polar polymers and improving the dispersion uniformity of each component in the matrix. The nucleating agent is 1,3:2,4-di(3,4-dimethylbenzyl)sorbitol, which forms tiny crystal nuclei during PE crystallization, inducing the polymer molecular chains to align orderly around them, accelerating the crystallization rate, refining the grain size, and improving the transparency and rigidity of the film. Furthermore, graphene nanosheets are hydroxylated or carboxylated... Surface modification with a base introduces polar functional groups to the surface, enhancing the interaction with the polymer matrix, improving the dispersion and interfacial bonding of graphene in the matrix, and allowing graphene to better exert its thermal conductivity, reinforcement, and other properties, thereby improving the overall performance of the film. By modifying the PE resin with a fluorinated polymer, which is either ethylene-tetrafluoroethylene copolymer or polyvinylidene fluoride grafted polyethylene, and with a fluorine content of 5-8% by mass, the film can have good chemical corrosion resistance, barrier properties, and surface hydrophobicity while ensuring a certain fluorine content, without excessively affecting the processing performance and mechanical properties of the PE matrix, thus achieving optimization of overall performance.

[0042] The crosslinking agent includes a crosslinking agent in which furan-functionalized polymers and maleimide-functionalized polymers are added to the polymer matrix simultaneously, triggering a diene addition reaction during processing to form a dynamic crosslinking network. The furan-functionalized polymer is furan methylamine-grafted polyethylene, and the maleimide-functionalized polymer is N-phenylmaleimide-terminated polyethylene. The composite antioxidant is composed of hindered phenolic antioxidants and phosphite antioxidants in a 1:1 mass ratio. The bio-based polyethylene is bio-based HDPE prepared by fermentation of sugarcane ethanol or corn starch, with a melt index of 2-5 g / 10 min.

[0043] Specifically, the crosslinking agent includes a furan-functionalized polymer and a maleimide-functionalized polymer simultaneously added to the polymer matrix. During processing, this crosslinking agent triggers a diene addition reaction to form a dynamic crosslinked network. The furan-functionalized polymer is furan methylamine-grafted polyethylene, and the maleimide-functionalized polymer is N-phenylmaleimide-terminated polyethylene. Thus, during processing, a reversible diene addition reaction occurs between the furan and maleimide groups, forming a dynamic crosslinked network with self-healing capabilities. At high temperatures, it can adaptively adjust its structure and release internal stress, thereby improving the elasticity, creep resistance, and dimensional stability of the film. Furthermore, the composite antioxidant consists of hindered phenolic antioxidants and phosphite antioxidants... The oxidants are compounded in a 1:1 mass ratio, so that the hindered phenolic antioxidants can capture free radicals and terminate the oxidation chain reaction, while the phosphite antioxidants can decompose peroxides. The two work synergistically to inhibit the oxidation reaction at different stages, thereby improving the antioxidant performance and service life of the film. Bio-based HDPE prepared by fermenting sugarcane ethanol or corn starch has a melt index of 2-5 g / 10 min. Bio-based HDPE has similar properties to traditional petroleum-based HDPE, while its source is renewable and meets environmental protection requirements. The suitable melt index gives it good processing fluidity, thereby improving production efficiency and reducing production costs while ensuring film performance.

[0044] The tea polyphenol-zinc complex is prepared by reacting tea polyphenols with zinc acetate in a molar ratio of 1:1 to 1:2. The nano silica has a particle size of 20-50 nm and is surface modified by silane coupling agent KH-550 or KH-570. The nano boehmite has a particle size of 50-100 nm and a mass ratio of 1:1.5 to 1:2 with LDH. The organotin-rare earth composite heat stabilizer is a mixture of dibutyltin dilaurate and cerium oxide in a mass ratio of 2:1 to 3:1.

[0045] Specifically, a tea polyphenol-zinc complex is prepared by reacting tea polyphenols with zinc acetate in a molar ratio of 1:1 to 1:2, thus forming a complex with a stable structure. This complex retains the antioxidant and antibacterial properties of tea polyphenols while enhancing their stability and activity through the action of zinc ions, more effectively delaying the oxidative degradation of the film and inhibiting the growth of microorganisms. The nano-silica particles have a diameter of 20-50 nm and are surface-modified with silane coupling agents KH-550 or KH-570. The small-diameter nano-silica has a larger specific surface area and surface activity, enabling better interaction with the polymer matrix. The silane coupling agent modification enhances the interfacial bonding between the nano-silica and the matrix, improving the mechanical strength and barrier properties of the film. Performance and wear resistance are achieved through the use of nano-boehmite with a particle size of 50-100nm and a mass ratio of 1:1.5-1:2 with LDH. The appropriate particle size and mass ratio allow nano-boehmite and LDH to work synergistically during combustion, improving the flame retardant and smoke suppression effects and enhancing the safety of the film under high-temperature cooking conditions. The organotin-rare earth composite heat stabilizer is a mixture of dibutyltin dilaurate and cerium oxide in a mass ratio of 2:1-3:1. Dibutyltin dilaurate has good thermal stability at lower temperatures, while cerium oxide can play an antioxidant and thermal stabilizing role at high temperatures. The combination of the two inhibits the thermal degradation reaction of the polymer in different temperature ranges, thereby improving the thermal stability and aging resistance of the film.

[0046] Please see the appendix Figure 1 A method for preparing a high-temperature resistant retortable PE film includes the following steps: S1. Processing: Metallocene polyethylene and bio-based polyethylene are placed in an oven and dried according to weight to remove moisture, resulting in a dried body. Nano-silica, graphene nanosheets, nano-boehmite, and layered double hydroxides are added to an appropriate amount of anhydrous ethanol and ultrasonically dispersed to achieve uniform dispersion, resulting in a dispersion. Fluoropolymer-modified PE resin, organotin-rare earth composite heat stabilizer, tea polyphenol-zinc complex, composite antioxidant, bio-based erucamide slip agent, calcium stearate, and nucleating agent are then mixed evenly using a high-speed mixer to obtain a mixture. In S1, the oven temperature is 80-100℃, the drying time is 2-4 hours, the ultrasonic dispersion frequency is set to 40-60kHz, the ultrasonic time is 30-60 minutes, and the high-speed mixer speed is 800-1200r / min for 15-30 minutes.

[0047] Specifically, metallocene polyethylene and bio-based polyethylene are dried in an oven according to their weight proportions to remove moisture and obtain a dried body. Nano-silica, graphene nanosheets, nano-boehmite, and layered double hydroxides are added to an appropriate amount of anhydrous ethanol and ultrasonically dispersed to achieve uniform dispersion, resulting in a dispersion. Fluoropolymer-modified PE resin, organotin-rare earth composite heat stabilizer, tea polyphenol-zinc complex, composite antioxidant, bio-based erucamide slip agent, calcium stearate, and nucleating agent are then mixed evenly using a high-speed mixer to obtain a mixture. This process removes moisture from the raw materials, preventing defects such as bubbles and pores during subsequent processing. Ultrasonic dispersion ensures uniform dispersion of nanomaterials and avoids agglomeration. High-speed mixing ensures uniform mixing of additives, providing high-quality raw materials for subsequent melt blending and ensuring that each component fully functions in the matrix.

[0048] S2, Blending: The dried material is fed into the main feed port of the twin-screw extruder, and the dispersion, mixture and compatibilizer are added into the twin-screw extruder through the side feeding device for full melt blending; the screw temperature of the twin-screw extruder in S2 is 180-220℃, the screw speed is 200-300r / min, the length-to-diameter ratio is 30-40, and the melt pressure is 8-12MPa.

[0049] Specifically, by feeding the dried material into the main feed port of a twin-screw extruder, and then adding the dispersion, mixture, and compatibilizer into the twin-screw extruder through a side feeder, the components are fully melt-blended. Under the high shear and high temperature of the twin-screw extruder, the components are fully mixed, and the compatibilizer promotes the compatibility between different polymers, forming a uniform polymer blend system, so that the performance of each component can be fully utilized and synergistically enhanced.

[0050] S3, Crosslinking: Dicumyl peroxide is dissolved in toluene to form a solution, which is then injected into a twin-screw extruder via a metering pump for initial crosslinking. A crosslinking agent is injected via another metering pump to initiate the crosslinking reaction. The crosslinking reaction time is controlled by adjusting the screw speed and the amount of crosslinking agent injected, and the material is obtained. The concentration of the solution in S3 is 10-15 wt%, the initial crosslinking area is in the temperature range of 150-170℃, and the crosslinking reaction time is 3-5 minutes.

[0051] Specifically, by dissolving dicumyl peroxide in toluene to prepare a solution, the solution is injected into a twin-screw extruder via a metering pump for initial crosslinking. A crosslinking agent is then injected via another metering pump to initiate the crosslinking reaction. The crosslinking reaction time is controlled by adjusting the screw speed and the amount of crosslinking agent injected, thus obtaining the material. In this specific temperature range, initial crosslinking is initiated by dicumyl peroxide, and the crosslinking agent further forms a dynamic crosslinking network. By controlling the crosslinking reaction time, the crosslinking density and network structure are controlled, thereby improving the thermal stability, mechanical properties, and dimensional stability of the film.

[0052] S4. Granulation: The twin-screw extruder is controlled to extrude the material, and granulation is carried out by water-cooled stringing or underwater pelletizing. The pelletizer speed is controlled according to the particle size requirements to obtain granules. The extrusion rate in S4 is 10-40 kg / h, and the pelletizer speed is 100-200 r / min.

[0053] Specifically, the material is extruded by controlling a twin-screw extruder, and granulated by water-cooled stringing or underwater pelletizing. The pelletizer speed is controlled according to the particle size requirements to obtain uniform granules, which are easy to store, transport and process. The appropriate extrusion rate and pelletizer speed ensure the quality and size uniformity of the granules, improving production efficiency and product quality stability.

[0054] S5. Film Formation: The granular material is fed into a casting machine to prepare a smooth film through the casting process. The film is then heat-treated in an oven to eliminate its internal stress and stabilize the dynamic cross-linking network, thus completing the preparation. In S5, the temperature of the casting machine is 180-210℃, the casting speed is 3-6m / min, the temperature of the cooling roller is 15-25℃, the temperature of the oven is 100-120℃, and the heat treatment time is 1-2 hours.

[0055] Specifically, by feeding granular material into a casting machine, a flat film is prepared through the casting process. The film is then heat-treated in an oven to eliminate internal stress and stabilize the dynamic cross-linking network, thus completing the preparation. The film prepared by the casting process has good flatness and thickness uniformity. The heat treatment eliminates the internal stress generated during the film forming process and stabilizes the dynamic cross-linking network, thereby improving the dimensional stability, optical properties, and mechanical properties of the film and ensuring that the film meets the requirements of high-temperature retort packaging materials.

[0056] The following is a further description with reference to specific embodiments: Example 1: A high-temperature resistant retortable PE film comprises the following raw materials in parts by weight: 60 parts metallocene polyethylene, 20 parts bio-based polyethylene, 1.2 parts dicumyl peroxide, 0.5 parts crosslinking agent, 4 parts nano silica, 3 parts layered double hydroxide, 1 part graphene nanosheets, 12 parts fluoropolymer modified PE resin, 1 part organotin-rare earth composite heat stabilizer, 0.4 parts tea polyphenol-zinc complex, 0.6 parts composite antioxidant, 6 parts compatibilizer, 0.8 parts bio-based erucic acid amide slip agent, 1 part calcium stearate, 0.4 parts nucleating agent, and 2 parts nano boehmite.

[0057] The compatibilizer includes maleic anhydride-grafted SEBS, the nucleating agent is 1,3:2,4-di(3,4-dimethylbenzylmethyl)sorbitol, the graphene nanosheets are surface-modified by hydroxylation or carboxylation, and the fluoropolymer-modified PE resin is ethylene-tetrafluoroethylene copolymer or polyvinylidene fluoride-grafted modified polyethylene, with a fluorine content of 6% by mass.

[0058] The crosslinking agent includes a crosslinking agent in which furan-functionalized polymer and maleimide-functionalized polymer are added to the polymer matrix simultaneously, triggering a diene addition reaction during processing to form a dynamic crosslinking network. The furan-functionalized polymer is furan methylamine-grafted polyethylene, and the maleimide-functionalized polymer is N-phenylmaleimide-terminated polyethylene. The composite antioxidant is composed of hindered phenolic antioxidant and phosphite antioxidant in a 1:1 mass ratio. The bio-based polyethylene is bio-based HDPE prepared by fermentation of sugarcane ethanol or corn starch, with a melt index of 3 g / 10 min.

[0059] The tea polyphenol-zinc complex was prepared by reacting tea polyphenols with zinc acetate in a molar ratio of 1:1.5. The nano silica particles had a particle size of 30 nm and were surface modified by silane coupling agent KH-550 or KH-570. The nano boehmite particles had a particle size of 60 nm and a mass ratio of 1:1.7 with LDH. The organotin-rare earth composite heat stabilizer was a mixture of dibutyltin dilaurate and cerium oxide in a mass ratio of 2:1.

[0060] A method for preparing a high-temperature resistant retortable PE film includes the following steps: S1. Processing: Metallocene polyethylene and bio-based polyethylene are placed in an oven and dried according to the weight ratio to remove moisture and obtain a dried body. Nano-silica, graphene nanosheets, nano-boehmite, and layered double hydroxide are added to an appropriate amount of anhydrous ethanol and ultrasonically dispersed to obtain a dispersion. Fluoropolymer-modified PE resin, organotin-rare earth composite heat stabilizer, tea polyphenol-zinc complex, composite antioxidant, bio-based erucic acid amide slip agent, calcium stearate, and nucleating agent are mixed evenly using a high-speed mixer to obtain a mixture. S2. Blending: The dried material is fed into the main feed port of the twin-screw extruder, and the dispersion, mixture and compatibilizer are added to the twin-screw extruder through the side feeding device for full melt blending; S3, Crosslinking: Dicumyl peroxide is dissolved in toluene to form a solution, which is then injected into a twin-screw extruder via a metering pump for initial crosslinking. A crosslinking agent is then injected via another metering pump to carry out the crosslinking reaction. The crosslinking reaction time is controlled by adjusting the screw speed and the amount of crosslinking agent injected, and the material is obtained. S4. Granulation: Control the twin-screw extruder to extrude the material, and granulate it by water-cooled stringing or underwater pelletizing. Control the pelletizer speed according to the particle size requirements to obtain granules. S5. Film Formation: The granular material is fed into a casting machine, and a flat film is prepared through the casting process. The film is then heat-treated in an oven to eliminate its internal stress, stabilize the dynamic cross-linking network, and complete the preparation.

[0061] In S1, the oven temperature is 90℃, the drying time is 3 hours, the ultrasonic dispersion frequency is set to 50kHz, the ultrasonic time is 50 minutes, the high-speed mixer speed is 1100r / min, and the mixing time is 20 minutes.

[0062] The screw temperature of the twin-screw extruder in S2 is 200℃, the screw speed is 250r / min, the length-to-diameter ratio is 35, and the melt pressure is 9MPa.

[0063] The concentration of the solution in S3 is 12wt%, the initial cross-linking region is in the region with a temperature of 160℃, and the cross-linking reaction time is 5 minutes.

[0064] The extrusion rate in S4 is 20 kg / h, and the pelletizer speed is 150 r / min.

[0065] The temperature of the casting machine in S5 is 200℃, the casting speed is 4m / min, the temperature of the cooling roller is 20℃, the temperature of the oven is 110℃, and the heat treatment time is 2 hours.

[0066] Example 2: The difference between this embodiment and Embodiment 1 above is that: A high-temperature resistant retortable PE film comprises the following raw materials in parts by weight: 50 parts metallocene polyethylene, 15 parts bio-based polyethylene, 0.8 parts dicumyl peroxide, 0.3 parts crosslinking agent, 3 parts nano silica, 2 parts layered double hydroxide, 0.5 parts graphene nanosheets, 8 parts fluoropolymer modified PE resin, 0.8 parts organotin-rare earth composite heat stabilizer, 0.2 parts tea polyphenol-zinc complex, 0.3 parts composite antioxidant, 4 parts compatibilizer, 0.5 parts bio-based erucic acid amide slip agent, 0.8 parts calcium stearate, 0.2 parts nucleating agent, and 1 part nano boehmite.

[0067] Example 3: The difference between this embodiment and Embodiment 1 above is that: A high-temperature resistant retortable PE film comprises the following raw materials in parts by weight: 55 parts metallocene polyethylene, 17.5 parts bio-based polyethylene, 1 part dicumyl peroxide, 0.4 parts crosslinking agent, 3.5 parts nano silica, 2.5 parts layered double hydroxide, 0.75 parts graphene nanosheets, 10 parts fluoropolymer modified PE resin, 0.9 parts organotin-rare earth composite heat stabilizer, 0.3 parts tea polyphenol-zinc complex, 0.45 parts composite antioxidant, 5 parts compatibilizer, 0.65 parts bio-based erucic acid amide slip agent, 0.9 parts calcium stearate, 0.3 parts nucleating agent, and 1.5 parts nano boehmite.

[0068] Table 1:

[0069] The table above compares traditional PE films. Table 1 shows that different contents of metallocene polyethylene improve heat resistance and mechanical properties, bio-based polyethylene balances environmental protection and flexibility, dicumyl peroxide and crosslinking agents regulate the crosslinking network, affecting dimensional stability and creep resistance, and the addition of nanomaterials such as nano-silica and graphene nanosheets increases the tensile and tear strength of the film and reduces oxygen permeability. Layered double hydroxides and nano-boehmite improve flame retardancy, the content of fluoropolymer-modified PE resin affects barrier properties and chemical stability, organotin-rare earth composite heat stabilizers, tea polyphenol-zinc complexes, and composite antioxidants respectively ensure thermal stability, antibacterial properties, and antioxidant properties, and reduce the yellowing index, compatibilizers ensure component dispersion, bio-based erucic acid amide slip agent and calcium stearate improve processing performance, and nucleating agents refine grains and improve transparency and rigidity. This solves the problems of traditional PE films during high-temperature cooking and long-term storage.

[0070] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A high-temperature resistant retortable PE film, characterized in that, The raw materials include the following parts by weight: 50-60 parts metallocene polyethylene, 15-20 parts bio-based polyethylene, 0.8-1.2 parts dicumyl peroxide, 0.3-0.5 parts crosslinking agent, 3-4 parts nano silica, 2-3 parts layered double hydroxide, 0.5-1 parts graphene nanosheets, 8-12 parts fluoropolymer modified PE resin, 0.8-1 parts organotin-rare earth composite heat stabilizer, 0.2-0.4 parts tea polyphenol-zinc complex, 0.3-0.6 parts composite antioxidant, 4-6 parts compatibilizer, 0.5-0.8 parts bio-based erucic acid amide slip agent, 0.8-1 parts calcium stearate, 0.2-0.4 parts nucleating agent, and 1-2 parts nano boehmite.

2. The high-temperature resistant retortable PE film according to claim 1, characterized in that: The compatibilizer includes maleic anhydride-grafted SEBS, the nucleating agent is 1,3:2,4-di(3,4-dimethylbenzylmethyl)sorbitol, the graphene nanosheets are surface-modified by hydroxylation or carboxylation, and the fluoropolymer-modified PE resin is ethylene-tetrafluoroethylene copolymer or polyvinylidene fluoride-grafted modified polyethylene, with a fluorine content of 5-8% by mass.

3. The high-temperature resistant retortable PE film according to claim 1, characterized in that: The crosslinking agent includes a crosslinking agent in which furan-functionalized polymer and maleimide-functionalized polymer are simultaneously added to the polymer matrix, triggering a diene addition reaction during processing to form a dynamic crosslinking network. The furan-functionalized polymer is furan methylamine-grafted polyethylene, and the maleimide-functionalized polymer is N-phenylmaleimide-terminated polyethylene. The composite antioxidant is composed of hindered phenolic antioxidant and phosphite antioxidant in a 1:1 mass ratio. The bio-based polyethylene is bio-based HDPE prepared by fermentation of sugarcane ethanol or corn starch, with a melt index of 2-5 g / 10 min.

4. The high-temperature resistant retortable PE film according to claim 1, characterized in that: The tea polyphenol-zinc complex is prepared by reacting tea polyphenols with zinc acetate in a molar ratio of 1:1 to 1:

2. The nano silica has a particle size of 20-50 nm and is surface modified by silane coupling agent KH-550 or KH-570. The nano boehmite has a particle size of 50-100 nm and a mass ratio of 1:1.5 to 1:2 with LDH. The organotin-rare earth composite heat stabilizer is a mixture of dibutyltin dilaurate and cerium oxide in a mass ratio of 2:1 to 3:

1.

5. A method for preparing a high-temperature resistant retortable PE film, characterized in that: The application of a high-temperature resistant retortable PE film according to any one of claims 1-4 includes the following steps: S1. Processing: Metallocene polyethylene and bio-based polyethylene are placed in an oven and dried according to the weight ratio to remove moisture and obtain a dried body. Nano-silica, graphene nanosheets, nano-boehmite, and layered double hydroxide are added to an appropriate amount of anhydrous ethanol and ultrasonically dispersed to obtain a dispersion. Fluoropolymer-modified PE resin, organotin-rare earth composite heat stabilizer, tea polyphenol-zinc complex, composite antioxidant, bio-based erucic acid amide slip agent, calcium stearate, and nucleating agent are mixed evenly using a high-speed mixer to obtain a mixture. S2. Blending: The dried material is fed into the main feed port of the twin-screw extruder, and the dispersion, mixture and compatibilizer are added to the twin-screw extruder through the side feeding device for full melt blending; S3, Crosslinking: Dicumyl peroxide is dissolved in toluene to form a solution, which is then injected into a twin-screw extruder via a metering pump for initial crosslinking. A crosslinking agent is then injected via another metering pump to carry out the crosslinking reaction. The crosslinking reaction time is controlled by adjusting the screw speed and the amount of crosslinking agent injected, and the material is obtained. S4. Granulation: Control the twin-screw extruder to extrude the material, and granulate it by water-cooled stringing or underwater pelletizing. Control the pelletizer speed according to the particle size requirements to obtain granules. S5. Film Formation: The granular material is fed into a casting machine, and a flat film is prepared through the casting process. The film is then heat-treated in an oven to eliminate its internal stress, stabilize the dynamic cross-linking network, and complete the preparation.

6. The method for preparing a high-temperature resistant retortable PE film according to claim 5, characterized in that: The temperature of the oven in S1 is 80-100℃, the drying time is 2-4 hours, the ultrasonic dispersion treatment is set to an acoustic frequency of 40-60kHz and an ultrasonic time of 30-60 minutes, and the high-speed mixer has a stirring speed of 800-1200r / min and a stirring time of 15-30 minutes.

7. The method for preparing a high-temperature resistant retortable PE film according to claim 5, characterized in that: The twin-screw extruder in S2 has a screw temperature of 180-220℃, a screw speed of 200-300 r / min, a length-to-diameter ratio of 30-40, and a melt pressure of 8-12 MPa.

8. The method for preparing a high-temperature resistant retortable PE film according to claim 5, characterized in that: The concentration of the solution in S3 is 10-15 wt%, the initial cross-linking region is in the region of 150-170℃, and the cross-linking reaction time is 3-5 minutes.

9. The method for preparing a high-temperature resistant retortable PE film according to claim 5, characterized in that: The extrusion rate in S4 is 10-40 kg / h, and the pelletizer speed is 100-200 r / min.

10. The method for preparing a high-temperature resistant retortable PE film according to claim 5, characterized in that: The temperature of the casting machine in S5 is 180-210℃, the casting speed is 3-6m / min, the temperature of the cooling roller is 15-25℃, the temperature of the oven is 100-120℃, and the heat treatment time is 1-2 hours.

Citation Information

Patent Citations

  • Metallocene polyethylene composition being easy to process and preparation method of same

    CN106554553A

  • Polyethylene composition for film and preparation method thereof

    CN117659552A

  • Lignin reversible cross-linked PE (polyethylene) plastic as well as preparation method and application thereof

    CN119081257A

  • Heat-resistant polyethylene composite packaging film and preparation method thereof

    CN119974717A